Exploring World’s Cyberbullying: It’s Implication on Social Marketing - Laela Nabilah; Asep Rifky Rahman Subagja; Fenfen Nurlita; Hilman Munawar; Vika Gustyana Mulyani (Prosiding Industrial Research Workshop and National Seminar, 2018)
Cyberbullying is an act of oppression to others to happiness in an appropriate way. Unlike the victim who feels unhappy due to depression, the bullies tend to feel happy and satisfied. In this study, we analyse the factors that make the number of cyberbullying in a country increase; there are Gross Domestic Product (GDP) and Human Development Index (HDI). Moreover, analysing happiness index as the factor that affected by cyberbullying is also conducted. The data were collected and analysed using the bivariate correlation analysis method. This study proved that GDP affects the HDI and then it will affect the number of cyberbullying in a country. Furthermore, a country’s happiness index is influenced by the number of cyberbullying cases. All of the findings are used to creating the most appropriate social marketing concept strategy. As a result, the social marketing will run as efficiently as possible, and the decreasing number of cyberbullying in a country will be achieved.